Effect of supplementation with black chokeberry (aronia melanocarpa) extract on inflammatory status and selected markers of iron metabolism in young football players: A randomized double-blind trial - Stankiewicz, B.; Cieslicka, M.; Mieszkowski, J.; Kochanowicz, A.; Niespodzinski, B.; Szwarc, A.; Waldzinski, T.; Reczkowicz, J.; Piskorska, E.; Petr, M.; Skarpanska-Stejnborn, A.; Antosiewicz, J. (Nutrients, 2023)
The use of herbal medicinal products and supplements in amateur and professional sports has increased in the last decades. This is because most of these products and supplements contain bioactive compounds with a variety of biological properties that exert a physiological effect on the human body. The aim of this study was to analyze the effect of dietary supplementation with lyophilized black chokeberry extract on the levels of pro-inflammatory cytokines, hepcidin, and selected markers of iron metabolism in a group of young football players. This double-blind study included 22 male football players (mean = 19.96 ± 0.56), divided into two groups: supplemented and placebo. Before and after a 90-day period of training combined with supplementation (6 g of lyophilized black chokeberry extract), participants performed maximal multistage 20-m shuttle run tests at the beginning and at the end of the supplementation period, with blood sampled for analysis at different times before and after exercise. The levels of IL-6, IL-10, ferritin, myoglobin, hepcidin, 8-OHdG, albumin, and TAC were analyzed. The analysis of variance revealed a significant effect of 90-day supplementation with the lyophilized extract on changes in the IL-6 and IL-10 levels, and TAC induced by maximal aerobic effort. In conclusion, supplementation with lyophilized black chokeberry extract improves the performance and antioxidant status of serum in humans and induces protective changes in inflammatory markers.